EFFECT OF PROCESS PARAMETERS ON THE MICROSTRUCTURE AND MECHANICAL PROPERTIES OF FRICTION-WELDED JOINTS OF AISI 1040/AISI 304L STEELS - Kirik, Ihsan; Ozdennr, Niyazi (Inst Za Kovinske Materiale I in Tehnologie, 2015)
Couples of AISI 304L and AISI 1040 steels were welded using the continuous-drive friction-welding process. The welded joints were manufactured using three different rotational speeds ((1300, 1500 and 1700) r/min), three different frictional pressures and three different frictional times. To determine microstructural changes, the interface regions of the welded samples were examined by scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive spectrometry (EDS). Microhardness and tensile tests of the welded samples were conducted. The results show that the properties of the microstructures are significantly changed and the interface temperature increased with the frictional time. An excellent tensile strength was observed for the joint made at a rotational speed of 1700 r/min and a frictional time of 4 s.
Keywords: friction welding; AISI 1040 steel; AISI 304L steel